Sleep quality, emotional moods, and cognitive outcomes among people living with HIV: An ecological momentary assessment study - Shan Qiao; Abhishek Aggarwal; Camryn Garrett; Arielle N’Diaye; Atena Pasha; Irene Esu; Chih-Hsiang Yang; Xiaoming Li (PLoS ONE, 2025)
Introduction Although studies have explored the relationship between sleep quality, mood, and cognitive outcomes among people living with HIV (PLWH), few use ecological momentary assessment (EMA) techniques to evaluate within-person associations between sleep quality and emotional/cognitive outcomes among PLWH at the day level. This study investigated the association between previous night’s sleep quality and momentary psychological outcomes in participants’ natural setting. Methods Study participants were PLWH in South Carolina who were at least 18 years old, diagnosed with HIV for at least 2 years, and able to operate a cellphone. Participants were sampled using posters posted in AIDS Service organizations, and snowball sampling. Data collection occurred between March and November 2023. During a 10-day EMA period, participants received 6 brief surveys throughout the day. Surveys were delivered within a 14-hour time window at semi-random times, with at least 1.5 hours between surveys. Five multilevel models were implemented with mindfulness, positive affect, negative affect, perceived cognition, and self-control as the outcome variables, and previous night’s sleep quality as the input variable. Results A total of 962 responses were gathered from 22 participants, with an average of 43.73 responses per person. Experiencing higher than usual levels of sleep quality the night prior had a significant positive association with higher levels of momentary mindfulness (β = 0.08, p < 0.001), positive affect (β = 0.1, p < 0.05), and self-control (β = 0.06, p < 0.05) when controlling for other covariates. Experiencing higher than usual levels of sleep quality the night prior exhibited trends towards a significant positive association with perceived cognition (β = 0.04, p < .1). Within-person sleep quality was not associated with momentary negative affect. Conclusion Among PLWH, future interventions targeting health behaviors sensitive to poor mood and cognition (e.g., ARV adherence) should incorporate intervention activities that ensure good sleep quality among participants. Additional studies are needed with larger sample sizes to assess the generalizability of study results.